Pharmacokinetics and Pharmacodynamics of the BACE1 Inhibitor Verubecestat (MK‐8931) in Healthy Japanese Adults: A Randomized, Placebo‐Controlled Study. Issue 5 (18th January 2019) - Chris Min, K.; Dockendorf, Marissa F.; Palcza, John; Tseng, Jack; Ma, Lei; Stone, Julie A.; Kleijn, Huub J.; Hodsman, Peter; Masuo, Kazuko; Tanen, Michael; Troyer, Matthew D.; van Vugt, Marianne; et al.
Abstract : β‐site amyloid precursor protein cleaving enzyme 1 (BACE1) is required for the production of β‐amyloid (Aβ) peptides and is considered a potential treatment target for Alzheimer's disease (AD). To support Japan's participation in the global clinical development program, we characterized the safety, pharmacokinetics (PKs), and pharmacodynamics of the BACE1 inhibitor verubecestat (MK‐8931) in 24 healthy Japanese adults in a two‐part, single‐center, randomized, placebo‐controlled phase I trial (protocol MK‐8931‐007) and compared the results with historical data from non‐Japanese subjects. Both single (20, 100, and 450 mg) and multiple (80 and 150 mg once daily for 14 days) doses of verubecestat were well tolerated. Verubecestat's PK profile was similar in Japanese and non‐Japanese subjects. Verubecestat also reduced mean cerebrospinal fluid concentrations of the Aβ proteins Aβ40, Aβ42, and soluble β fragment of amyloid precursor protein; the level of reduction was comparable between Japanese and non‐Japanese subjects. These results support the continued global development of verubecestat as a potential disease‐modifying agent for Japanese and non‐Japanese subjects who are at risk for developing AD.